2009
DOI: 10.1002/gps.2193
|View full text |Cite
|
Sign up to set email alerts
|

Association between cognition and daily life functioning in dementia subtypes

Abstract: The association between cognition and daily life functioning varied among dementia subtypes for AD, VaD, FTD and PD. Furthermore, the overall scores on both domains differ between dementia subtypes, indicating that different types of dementia are characterized by a specific pattern of cognitive status and daily life functioning. These findings underline the need for multidomain assessment in patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…In our study, cognition was significantly associated with ADL. These results are consistent with those from previous studies conducted with the CERAD total score [22] or other cognitive measures [4, 5, 7, 8, 9]. Women received better scores in the ADCS-ADL, which probably reflects the traditional way to share housework in marriages in this generation, and this needs to be taken into account when using ADL measures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, cognition was significantly associated with ADL. These results are consistent with those from previous studies conducted with the CERAD total score [22] or other cognitive measures [4, 5, 7, 8, 9]. Women received better scores in the ADCS-ADL, which probably reflects the traditional way to share housework in marriages in this generation, and this needs to be taken into account when using ADL measures.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, neuropsychiatric symptoms, such as depression, apathy and agitation, seem to be common already in early stages of AD and can have an impact on both patients’ and care-givers’ well-being [1, 2, 3]. Cognitive performance has been consistently associated with functional ability [4, 5, 6, 7, 8]; however, the association of neuropsychiatric symptoms with cognition and daily functioning is unclear [7, 9, 10, 11, 12, 13], in spite of the fact that the amount of neuropsychiatric symptoms seems to increase in patients with more advanced dementia [14, 15]. Thus, more information is needed to elucidate how these features of AD are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, there has been limited research investigating ADLs in other dementias. Recent studies have shown that patients with PNFA are not as functionally impaired as patients with AD [9], and that cognition is more affected than ADLs [11]. Behavioural disturbances are also present in patients with PNFA [12][13][14], although ADLs in PNFA, LPA and AD they were not reported as being significantly disturbing by their carers.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, ADL measurements differ in their responsiveness to drugs and psychosocial interventions depending on the state of dementia (Desai et al, 2004;Sikkes et al, 2009;Bouwens et al, 2009;Gauthier et al, 2010;Voigt-Radloff and Hüll, 2011). Low correlations of cognition not only with the IDDD but also with the other ADL measurements (PRPP; ADCS-ADL; Table 6) emphasize the conceptual differences between these constructs.…”
Section: Activities Of Daily Livingmentioning
confidence: 98%